Relational Contractions of Matkowski–Berinde–Pant Type and an Application to Certain Fractional Differential Equations - Doaa Filali; Faizan Ahmad Khan; Adel Alatawi; Esmail Alshaban; Montaser Saudi Ali; Fahad M. Alamrani (Fractal and Fractional)
This paper concludes a few fixed-point outcomes involving almost Matkowski contraction-inequality of Pant type in a relational metric space. The findings established here enhance, expand, consolidate and develop several noted outcomes. In order to argue for our investigations, we construct some illustrative examples. We exploit our outcomes to analyze the availability of a (unique) positive solution to certain singular fractional differential equations.